Esistere, ossia viaggiare. La visione metaforica della vita in 'Non c’è dolcezza' di Anilda Ibrahimi - Karp, Karol (Incontri. Rivista europea di studi italiani, 2015)
Live and travel. The metaphorical vision of life in the novel Non c’è dolcezza by Anilda Ibrahimi The essay, divided into two parts, aims to investigate the motif of journey in the novel Non c’è dolcezza by Anilda Ibrahimi, a migrant author of Albanian origin. The journey is considered mainly as a metaphor for the existence of the characters, who often seem to be puppets completely controlled by fate. These characters “travel” both together (Lila, Eleni) and individually (Arlind, Andrea) in order to determine their identity, realize the dreams which would let them feel happy and forget the problems faced in their everyday lives. Analysis shows that happiness is often impossible because human life is full of negative factors which provoke an existential failure; the message transmitted by Ibrahimi is very pessimistic. The theoretical basis of the article is constituted by the works of such scholars as Theodor Adorno, Giorgio Agamben, Henri Bergson, Roland Barthes, Sigmund Freud, Leszek Kołakowski, Julia Kristeva and Paul Ricoeur.